Corporate Social Responsibility (CSR) As Post-Mining Environmental Protection: An Integrative Normative Study Between Environmental Fiqh and Positive Law In Indonesia - Mustangin, Muhammad (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Corporate Social Responsibility (CSR) in the mining sector has become an important instrument in efforts to protect and preserve the environment. This article aims to examine normatively integratively how CSR is positioned within the framework of Indonesian positive law and environmental fiqh as a form of social and ecological responsibility of mining companies. The research method used is normative research. This article finds that in national law, CSR is regulated in Law No. 40 of 2007 concerning Limited Liability Companies and its derivative law in the form of PP No. 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies. On the other hand, environmental fiqh offers moral and ethical foundations based on maqashid sharia that emphasizes the prohibition of damage (ifsad) and the obligation to maintain the balance of nature hifdz al-bi'ah). Integration between these two normative systems can form a paradigm of environmental protection that is not only legal-formal, but also spiritual-ethical. This article recommends strengthening the CSR of mining companies with an Islamic values approach to create ecological justice and environmental sustainability.